STUDENTS’ ERRORS ANALYSIS IN CHANGING ACTIVE VOICE INTO PASSIVE VOICE OF SIMPLE PRESENT AND PAST TENSE (A CASE STUDY AT EIGHTH GRADE OF SMP SWASTA PUTERI SION MEDAN) - Dian Septiana Manurung; Lince Lestari; Monica Evaliani Manik (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2020)
Abstract This research was purposed to analyze students’ errors in changing active into passive voice of simple present and past tense. This study used descriptive qualitative research design. The data source was students’ test printed papers which contained passive voice questions as the instrument. The subject was eighth grade of SMP Swasta Puteri Sion Medan which consisted of 31 students. The data was identified, classified, and analyzed based on surface strategy taxonomy of Dulay’s theory, namely error of omission with percentage 23,3%, error of addition with percentage 12,19%, error of misformation with percentage 55,82% which established as the dominant error, and error of misordering with percentage 8,67%. The total of errors’ percentage reached 99,98%. Keywords: Error Analysis, Passive Voice. Abstrak Penelitian ini bertujuan untuk menganalisis kesalahan siswa dalam mengubah kalimat aktif menjadi kalimat pasif dalam simple present dan past tense. Penelitian ini menggunakan desain penelitian deskriptif kualitatif. Sumber data adalah lembar kerja siswa yang dicetak yang berisi pertanyaan kalimat pasif sebagai instrumennya. Subjek penelitian ini adalah kelas VIII SMP Swasta Puteri Sion Medan dengan jumlah siswa sebanyak 31 orang. Data diidentifikasi, diklasifikasikan, dan dianalisis berdasarkan kesalahan taksonomi siasat permukaan dari teori Dulay, yaitu kesalahan penghilangan dengan persentase 23,3%, kesalahan penambahan dengan persentase 12,19%, kesalahan salah formasi dengan persentase 55,82% yang ditetapkan sebagai kesalahan dominan dan kesalahan salah susun dengan persentase 8,67%. Total persentase kesalahan mencapai 99,98%. Kata kunci: Analisis kesalahan, kalimat pasif.